Exploratory analysis of the association between body composition albumin-bound paclitaxel induced peripheral neuropathy - Jiang, Ying; Guo, Jiayuan; Zhao, Juan; Chen, Feng; Hou, Jixiang; Li, Xiaorong; Li, Zhenhao; Jin, Gaowa; Li, Quanfu (Frontiers in Pharmacology, 2026)
ObjectiveThis study aimed to examine the relationship between L3 Skeletal Muscle Index (L3SMI) and the incidence and severity of chemotherapy-induced peripheral neuropathy (CIPN) in patients with malignant tumors treated with nab-PTX (albumin-bound paclitaxel) monotherapy or in combination with cisplatin or carboplatin.MethodsThis study included 52 patients with complete clinical data. The patients’ baseline demographics, disease characteristics, body composition, PG-SGA scale and chemotherapy regimens,was evaluated prior to chemotherapy initiation. Blood samples were collected within 1 hour following the final nab-PTX dose. CIPN was assessed before the third chemotherapy cycle. Patients receiving nab-PTX doses on day 1 were categorized into Group A (n = 36), while those receiving doses on days 1 and 8 were assigned to Group B (n = 16). Group A was further divided into the sarcopenia subgroup (A1) and the non-sarcopenia group (A2), while Group B was divided into the sarcopenia subgroup (B1) and the non-sarcopenia subgroup (B2). The relationship between L3SMI, CIPN incidence and severity were analyzed, and the impact of L3SMI on blood drug concentrations was also investigated.ResultsThe pathological types of enrolled patients included: lung cancer, esophageal carcinoma, cervical cancer, and ovarian cancer. The incidence of CIPN ≥ B grade was significantly higher in sarcopenia subgroups compare with non-sarcopenia in Group A (A1 vs. A2, P = 0.042). Severe CIPN (defined as ≥ grade C) showed a numerically higher occurrence in the sarcopenia subgroups compared to their non-sarcopenia counterparts across groups, although these comparisons did not reach statistical significance. Furthermore, the incidence of CIPN was significantly higher in Group A than in Group B. Among patients receiving nab-PTX doses on day 1, the average dose per kilogram of lean body mass (LBM) was significantly greater in the sarcopenia subgroup compared to the non-sarcopenia subgroup (P < 0.001).ConclusionSarcopenia significantly increases the incidence and severity of CIPN in patients undergoing nab-PTX-based chemotherapy. This association may be attributed to the effectively higher dose of nab-PTX per kilogram of lean body mass in patients with sarcopenia, despite the absence of a direct correlation between L3SMI and measured blood drug concentrations. These findings highlight the importance of body composition assessment prior to chemotherapy, as patients with sarcopenia may require enhanced monitoring for CIPN or individualized dosing considerations.